Optimization of Cellular Concrete Formulation with Aluminum Waste and Mineral Additions - Bouglada, Mohammed Salah; Ammar, Noui; Larbi, Belagraa (Salehan Institute of Higher Education, 2021)
The paper aims to study cellular concrete with a new approach of formulation without an autoclave, with the use of aluminum waste and incorporation of mineral additions into the sand and evaluate its physical and mechanical properties. In this experimental study, two types of cellular concrete are prepared, based on crushed and dune sand with the incorporation of 15% of the slag and 10% of pozzolana, as sand replacement. An experimental program was performed to determine the compressive strength at 28 days, the density and thermal conductivity of the confected cellular concrete. The obtained results showed that concretes prepared with crushed sand developed better mechanical resistance compared to the dune sand. It is also noted that the concretes containing the mineral additions provide a substantial increase in compressive strength in particular slag. Furthermore, cellular concretes with sand dunes offer better thermal conductivity, compared to those with crushed sand. The use of the additions reduces the Water/Binder (W/B) ratio and leads to a lower thermal conductivity regardless of the used sand nature. The outcome of the present study here in could present a modest contribution for the production of cellular concrete with local materials in particular dune sand, active mineral addition and aluminum waste. The physical and mechanical properties obtained from this new composition are estimated acceptable compared to those of the industry-prepared cellular concrete product.Â Doi: 10.28991/cej-2021-03091721 Full Text: PDF